A review of using porous ashalt pavement as an alternative to conventional pavement in stormwater treatment. - Ahmad, Kabiru Abdullahi; Abdullah, Mohd Ezree; Abdul Hassan, Norhidayah; Ahmad Daura, Hussaini; Ambak, Kamarudin (Emerald Publishing Limited, 2017)
Porous asphalt has been used for than 50 years, but it was originally developed in 1970 at Franklin institute in Philadelphia, Pennsylvania and by 1974 the first formalized procedure was created by the federal highway administration to design mixtures. Many researches on porous asphalt mixture have been conducted for the past two decades. However, there remains some concern about the potential adverse impacts of infiltrated surface water on the underlying groundwater. This paper is a review of the use of porous asphalt pavement. In this study, a critical review on history and benefits is presented followed by review of general studies of using porous asphalt pavement, and some recent scientific studies that examine potential contamination of soil and groundwater due to infiltration systems. The researches indicate that porous asphalt pavement is more efficient than conventional pavements in terms of retaining pollutants, improving the quality of water and runoff while maintaining infiltration.